Little town on the prairie - Wilder, Laura Ingalls, 1867-1957.; Williams, Garth (New York : HarperTrophy, An Imprint of HarperCollinsPublishers, 1981)
Pa's homestead thrives, Laura gets her first job in town, blackbirds eat the corn and oats crops, Mary goes to college, and Laura gets into trouble at school, but becomes a certified school teacher.
"First published in 1941. Revised edition, illustrated by Garth Williams, published in 1953."
Keywords: Wilder, Laura Ingalls, -- 1867-1957 -- Juvenile fiction; Frontier and pioneer life -- Juvenile fiction; Families -- Juvenile fiction; Frontier and pioneer life -- Fiction; Family life -- Fiction; Adventure fiction